Women’s Sexual and Reproductive Health: A Comparative Study on the Levels of Knowledge and Attitude About Them Among Urban and Rural Women from Selected Areas of Bangladesh - Giasuddin, Abu Sayed Mohammad; Banu, Laila Arjumand; Annei, S. N Tahmina Karim; Tamanna, Tasnim; Harun, Maha; Parveen, N. T (British Journal of Healthcare and Medical Research, 2024)
Background: Women’s sexual and reproductive health has been a great concern for every woman and it is an integral part of their overall health. Not much studies in this area of research were done and reported from Bangladesh; Objectives: In the present study, objectives were therefore to know the levels of knowledge and attitude regarding women’s sexual and reproductive health among the Urban and Rural women from selected areas of Bangladesh; Methodology: This cross-sectional study was conducted among purposely selected 218 women of reproductive age from Urban (n=109, 20-45 years, Mean ± SD: 32.16 ± 8.22 years) and Rural (n=109, 18-40 years, Mean ± SD: 30.83 ± 9.23 years) selected areas of Bangladesh. The data were collected by using structured questionnaire organized in three sections i.e. Section-01: Socio-demographic information, Section-02: Knowledge levels on components of women’s sexual and reproductive health. Section-03: Attitude towards sexual and reproductive health. The data were analyzed by appropriate by statistical methods i.e. Student’s t-test and Chi-squared test, using SPSS programme and the results were presented in three sections accordingly; Results: Among Urban women, 94 (86.2%), 11(10.1%) and 4 (3.7%) and Rural women, 65 (59.6%), 32 (29.4%) and 12 (11.0%) were Muslims, Hindus and others respectively (p<0.001). Urban women had much higher educational levels compare to rural women respondents (p<0.001). And occupations of Urban women were mostly teaching and office jobs, whereas Rural women were mostly house wives and garments factory workers (p<0.001). Monthly income of Urban women as well as their family income both were much higher compared to Rural women (p<0.001). Majority of respondents belonged to single family [Urban: 73 (66.9%), Rural: 63 (57.8%)] compared to joint family type [Urban: 37 (33.1%), Rural: 46 (42.2%)] (p>0.1). About family planning, Urban women showed better knowledge levels than Rural women [Urban: Poor- 03 (2.8%), Moderate-11 (10.1%), Good-73 (66.9%), Very Good-22 (20.2%); Rural: Poor-24 (22.1%), Moderate-82 (75.2%), Good-3 (2.7%), Very Good-0 (0.0%)] (p<0.001). On contraception usage, Urban women showed much better knowledge than Rural women [Urban: Poor- 01 (0.9%), Moderate-18 (16.6%), Good-73 (66.9%), Very Good-17 (15.6%); Rural: Poor- 65 (59.6%), Moderate-43 (39.7%), Good-1 (0.5%), Very Good-0 (0.0%)] (p<0.001). Knowledge levels on care during pregnancy of Urban women ware at higher levels compared to Rural women [Urban: Poor-03 (2.8%), Moderate-16 (14.6%) Good-72 (66.1%), Very Good-18 (16.5%); Rural: Poor-12 (11.1%), Moderate-95 (87.1%) Good-02 (1.8%), Very Good-0 (0.0%)] (p<0.001). Levels of Knowledge were also found to much better for Urban compared to Rural women on safe motherhood [Urban: Poor-05 (4.6%), Moderate-11 (10.1%) Good-78 (71.6%), Very Good-15(13.7%); Rural: Poor-29 (26.6%), Moderate-78 (71.6%) Good-02 (1.8%), Very Good-0(0.0%)] (p<0.001); New born care [Urban: Poor-02 (1.8%), Moderate-22 (20.2%) Good-73 (66.9%), Very Good-12 (11.1%); Rural: Poor-26 (23.8%), Moderate-81 (74.4%) Good-02 (1.8%), Very Good-0 (0.0%)] (p<0.001); Abortion [Urban: Poor-08 (7.3%), Moderate-41 (37.6%) Good-57 (52.3%), Very Good-3 (2.8%); Rural: Poor-81 (74.4%), Moderate-26 (23.8%) Good-02 (1.8%), Very Good-0(0.0%)] (p<0.001) and birth spacing [Urban: Poor-0 (0.0%), Moderate-35 (32.2%) Good-61 (55.9%), Very Good-13 (11.9%); Rural: Poor-27 (24.8%), Moderate-81 (74.3%) Good-01 (0.9%), Very Good-0(0.0%)] (p<0.001). Regarding attitude towards sexual and reproductive health, no significant differences were observed between Urban and Rural respondents on importance to avoid pregnancy [Urban: Yes-97 (88.9%), No-12 (11.1%), NA-0 (0.0%); Rural: Yes-95 (87.2%), No-14 (12.8%), NA-0 (0.0%)] (p>0.25), Oral contraceptive fills usage [Urban: Yes-65 (59.6%), No-44 (40.4%), NA-0 (0.0%); Rural: Yes-60 (55.1%), No-49 (44.9%), NA-0 (0.0%);] (p>0.5), IUDs usage to prevent pregnancy [Urban: Yes-3 (2.8%), No-106 (97.2%), NA-0 (0.0%); Rural: Yes-0 (0.0%), No-109 (100%), NA-0 (0.0%)] (p>0.1). However, attitude of Urban women were significantly positive compared to Rural respondents towards (i) usage of condoms during sexual intercourse [Urban: Yes-59 (54.1%), No-50 (45.9%), NA-0 (0.0%); Rural: Yes-20 (18.3%), No-89 (81.7%), NA-0 (0.0%)] (p<0.001); (ii) unwanted pregnancy [Urban: Yes-6 (5.5%), No-103 (94.5%), NA-0 (0.0%); Rural: Yes-24 (22.1%), No-85 (77.9%), NA-0 (0.0%)] (p<0.005) and usage of different contraceptive methods in life time [Urban: Yes-72 (66.1%), No-37 (33.9%), NA-0 (0.0%); Rural: Yes-10 (9.2%), No-99 (90.8%), NA-0 (0.0%)] (p<0.001). Significantly large number of respondents, both Urban and Rural, did not hear about affordable care act (ACA) introduced by Federal Government of USA in March 2010 [Urban: Yes-01 (0.9%), No-108 (99.1%), NA-0 (0.0%); Rural: Yes-0 (0.0%), No-109 (100%), NA-0 (0.0%)] (p>0.5); Conclusions: Our findings clearly suggested that Rural women were far behind compared to Urban women about the levels of knowledge on, and attitude towards, women’s sexual and reproductive health. Therefore, national programmes and interventions are needed and be introduced through appropriate agencies to address the challenges in this field for communities in Bangladesh. In addition, greater policy focus should be directed towards women’s and empowerment factors for better knowledge and attitude about women’s sexual and reproductive health leading to much improved status in this area in Bangladesh.